THE EFFECT OF GOOD CORPORATE GOVERNANCE ON FINANCIAL PERFORMANCE AT PT. MATAHARI DEPARTMENT STORE Tbk. - islamiah, muslimah; Pratiwi, Aliah (Perpustakaan dan Penerbitan Unismuh Makassar, 2019)
This study aims to empirically prove the presence or absence of the influence of corporate governance (Board of directors, Board of Commissioners' Size,and Audit Committee) on financial performance at PT. Matahari department store Tbk. The method of analysis of this study uses multiple linear regression and the classical assumption test. The number of samples used in this study is 10 years in the period 2009 - 2018 taken through purposive sampling. The results of this study indicate that (1) the board of directors not influential significant effect on ROA, (2) the size of the board of commissioners not influential significant effect on ROA, (3) The audit committee is influential and not significant to ROA.